Serumpun dalam Satu Akidah: Pelaksanaan Tabligh Akbar di Desa Barung-Barung, Kecamatan Lima Puluh Pesisir, Kab. Batu Bara - Fadhilah, Mhd. Fajar; Sabilla, Sabna; Syafira, Sherly; Nasution, Hafizah Mahira; Albina, Meyniar (Civiliza Publishing, 2024)
The implementation of tabligh akbar is a significant activity in the religious life of Muslim communities in Indonesia, serving as a means to strengthen doctrinal understanding and community cohesion. This study aims to analyze the implementation of tabligh akbar in Desa Barung-Barung, Lima Puluh Pesisir District, Batu Bara Regency, and its impact on social cohesion and the reinforcement of community faith. The methodology used is a qualitative approach with in-depth interviews and participatory observation techniques. The results show that the tabligh akbar in this village successfully strengthened community solidarity and enhanced religious understanding. The article concludes that tabligh akbar serves not only as a medium for preaching but also as an effective social binder.